Analisis Hook Rate Pancing Rawai Dasar di Sekitar Perairan Laut Banda, Buton Utara - Ander Ibrahim; Naslina Alimina; Abdullah Abdullah; Hasnia Arami; Syamsul Kamri (Universitas Halu Oleo, 2022)
This study aims to determine the value of the bottom long line which is operated around thei Banda Sea waters, North Buton Regency. Data collection is carried out from October to November 2021 using participatory observation techniques in fishing activities. The data collected consisted of the dimensions and operating techniques of fishing gear and the number of fish caught on each fishing trip for 30 trip. The results showed that the hook rate on each trip varied from 3 percent to 22 percent with an average value of 10.37 percent.